Endogenous incomplete markets, enforcement constraints, and intermediation - Arpad Abraham; Eva Carceles-Poveda (Theoretical Economics, 2006)
Alvarez and Jermann (2000) show that the constrained efficient allocations of endowment economies with imperfect risk sharing due to limited commitment can be decentralized as competitive equilibria with endogenous debt constraints that are not too tight. These are the loosest possible borrowing limits that do not allow for default in equilibrium. However, such a decentralization is not possible in the presence of capital accumulation, since changes in the aggregate capital also affect the incentives to default. In a model with endogenous production, aggregate risk, and competitive intermediaries, we show that a decentralization with endogenous debt constraints is possible if one also imposes an upper limit on the intermediaries' capital holdings.
Keywords: E44; D52; G12; 330; Complete markets; enforcement constraints; intermediation